2017
DOI: 10.1111/bcpt.12788
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Genetic Variants in the Glucocorticoid Receptor Signalling Pathway in Autoimmune Hepatitis with Failure of Standard Treatment

Abstract: The standard treatment for autoimmune hepatitis (AIH) is predniso(lo)ne for remission induction, tapered and followed by azathioprine, which effectively controls the disease in the majority of patients. However, some patients prove to be unresponsive or non-tolerant and require alternative immunosuppressive regimens for disease control. We aimed to investigate whether these AIH patients who experience failure of standard treatment have a genomic basis for their problem in the form of pharmacogenetic variants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Glucocorticoid receptors exert their action through cellular effects and gene transcription. The signaling of glucocorticoids (GCs) is coupled to various pathways (Eriksen et al, 2017). Glucocorticoids act by binding to glucocorticoid receptors intracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid receptors exert their action through cellular effects and gene transcription. The signaling of glucocorticoids (GCs) is coupled to various pathways (Eriksen et al, 2017). Glucocorticoids act by binding to glucocorticoid receptors intracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…It has been discovered that several mechanisms contribute to the great heterogeneity of glucocorticoid receptor protein among individuals, such as genetic polymorphisms in the glucocorticoid receptor gene . Recently, a study from Denmark found that the insensitivity to steroids in patients with AIH had a close association with genetic polymorphisms in the glucocorticoid receptor‐signaling pathway . Nevertheless, much more evidence is still needed to guide the clinical use of steroids according to the genetic polymorphisms of patients.…”
Section: Pharmacogenetics and Precision Medicationmentioning
confidence: 99%